Last man in tower : a novel - Adiga, Aravind (New York : Alfred A. Knopf, 2011)
Refusing to leave his home when a powerful real-estate developer offers to buy out the residents of a crumbling apartment complex near the infamous Dharavi slums, a retired schoolteacher becomes a target of violence by the developer and his own neighbors.
Keywords: Apartment dwellers -- India -- Fiction; Apartment houses -- India -- Fiction; Real estate developers -- India -- Fiction; Social conflict -- India -- Fiction